EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN SIMBOLIK MODELING UNTUK MENINGKATKAN PEMAHAMAN PERILAKUSEKSUAL SEHAT REMAJA - Yusuf Maulana; Elya Helmi (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2017)
EffectivinessGroup Guidance ServiceWithsymbolik modeling TechniquesFor Increaseing pemahaman seksualsehat Students Of Grade XISMK AsSa’adah pondok kelapa.Skripsi.Program Study Guidance andCounseling Faculty Teaching ScienceEducation Universitas IslamAsyafiiyahThis research is motivated bythe importance of the students whohave high confidence, to be able tocarry out tasks and solve problems,especially learning so that studentsachieve a certain field and successfulin the future.The purpose of this study is toobtain empirical data and informationabout the effectiveness of guidanceservices group with symbolikmodeling techniques to increase theclass XISMK As-Sa’adah pondokkelapa.The research is QuasiExperimental Design with researchdesign non equivalent control groupdesign. Subjects of this research arethestudents of grade XI SMK As-Sa’adahpondok kelapa the academic year of2016/2017who have lowSelfConfident. The subjects numbering 70persons. This subject will be dividedinto two groups of 35 persons into theexperimental group and 35 personscontrol group. The collectiontechnique of data use self confidentquestionnaire. Validate data useproduct moment of ms. Exel. Theanalysis of the data in this research uset-test formula with ms.Exel andcalculation manual.The result of the analysisshowed thitung= 0,257 ttabel= 1,667dengan taraf signifikan (α = 0,05)dk =n1 + n2 -2 = 35 + 35 – 2 = 68. For resultresearch seen that ttest ≥ ttable.Hipotesisnihil (Ho) to explain “Groupguidance service with symbolikmodeling techniques not effectiveforincreaseing pemahaman seksual sehatof grade XISMK A-Sa’adah pondokkelapa ” rejecting”.